Shifting the Earth the mathematical quest to understand the motion of the universe - Mazer, Arthur, 1958- (Wiley, 2011)
"Combining history, astronomy, and philosophy, this insightful book demonstrates how mathematics evolved and was used to explain planetary movements based on centuries of manual observations and careful data collection. Historical and social contexts behind the mathematical advances are provided, and the history includes the larger political and philosophical environment that affected the lives of the contributing scientists. A prime objective is to illustrate how Kepler's heliocentric pathway evolved from Ptolemy's geocentric model, with Copernicus as the critical intermediary. This reference will be valuable to science and mathematics enthusiasts, and will serve as a textbook or supplemental recommended reading for undergraduates"--